2006
DOI: 10.1007/s00520-006-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Financial and family burden associated with cancer treatment in Ontario, Canada

Abstract: These results suggest the financial burden is problematic for 20% of this sample. The caregivers' lost time from work influence this burden, and for 36% of this sample, it amounts to one third of their working days in any given month. Policies and programs to address these gaps are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
172
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(189 citation statements)
references
References 19 publications
(23 reference statements)
10
172
3
4
Order By: Relevance
“…Our study sought preliminary information about outof-pocket patient costs, an outcome that has not previously been reported in hnc. Out-of-pocket expenses reported by our patients were higher than those reported for adult patients with other solid tumours 11,19 . However, lost time from work among our study patients was similar to time lost by breast cancer patients 29,30 .…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Our study sought preliminary information about outof-pocket patient costs, an outcome that has not previously been reported in hnc. Out-of-pocket expenses reported by our patients were higher than those reported for adult patients with other solid tumours 11,19 . However, lost time from work among our study patients was similar to time lost by breast cancer patients 29,30 .…”
Section: Discussioncontrasting
confidence: 78%
“…To explore out-of-pocket costs incurred by hnc patients, we noted and compared the responses to p-safe items by study patients with published data from other adult patients treated in Ontario for cancers other than hnc 11,19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent telephone interview study of 453 Canadian breast cancer patients who worked during cancer treatment showed a 27% average reduction in earned wages in the first year following a cancer diagnosis (Lauzier et al, 2008). In addition, family members may have to reduce paid work to accommodate treatment schedules, emotional needs, and other demands, such as providing support and care for the family member receiving treatment (Longo et al, 2006). Family caregivers of terminal cancer patients suffer job loss and severe work-related difficulties, probably due to caregiving itself and to fatigue (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Time after cancer diagnosis plays a role in the financial burden in households as well; other studies have provided evidence that both direct and indirect factors contribute to patient costs (Houts et al, 1984;Stommel et al, 1993;Guidry et al, 1998;Longo et al, 2006). However, there are very few studies that have investigated the impact of direct or indirect medical expenses and change in economic status on the household and their relationship to catastrophic health expenditure.…”
Section: Introductionmentioning
confidence: 99%